2017
DOI: 10.1080/09540121.2017.1366415
|View full text |Cite
|
Sign up to set email alerts
|

Behavior change following HIV diagnosis: findings from a Cohort of Los Angeles MSM

Abstract: The effect of an HIV diagnosis on subsequent behavior of men who have sex with men (MSM) remains unclear. From 2009 - 2012 he NIDA funded Metromates Study enrolled and followed for one year MSM seeking testing for HIV in Los Angeles, assessing those with new HIV diagnoses for acute/recent HIV infection. Behavioral data were collected via Computer-Assisted Self-Interview from 321 men of whom 125 were classified as recently HIV infected, 91 as not recently HIV infected, and 105 as HIV-negative. Differences over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…A high rate (6.6 per 100 PYFU) of incident STIs has been found among patients with acute HIV infection7 and patients who continued to practice condomless anal intercourse after being diagnosed as having HIV infection 32. In this study, the incidence of any STI before the achievement of viral suppression was higher in patients without rapid ART initiation than it was in those with rapid ART initiation (28.3 vs 18.8 per 100 PYFU) within a short follow-up duration; this thus raises concerns that STIs may facilitate HIV transmission through genital secretions with relatively high HIV RNA loads 33 34.…”
Section: Discussionmentioning
confidence: 99%
“…A high rate (6.6 per 100 PYFU) of incident STIs has been found among patients with acute HIV infection7 and patients who continued to practice condomless anal intercourse after being diagnosed as having HIV infection 32. In this study, the incidence of any STI before the achievement of viral suppression was higher in patients without rapid ART initiation than it was in those with rapid ART initiation (28.3 vs 18.8 per 100 PYFU) within a short follow-up duration; this thus raises concerns that STIs may facilitate HIV transmission through genital secretions with relatively high HIV RNA loads 33 34.…”
Section: Discussionmentioning
confidence: 99%
“…A Mathematical modelling study also reveals substantial risky behaviour reduction among post‐diagnosis MSM in Southern California . However, a recent study in Los Angeles indicates a higher prevalence of condomless anal sex among recently seroconverted MSM compared to that before HIV diagnoses . Per the China CDC guidelines, our study participants received both pre‐test and post‐test counselling in safer sex provided by healthcare staff; participants in the intervention arm received both SOC and peer counselling.…”
Section: Discussionmentioning
confidence: 96%
“…This sample was obtained by recruiting individuals who sought HIV testing and the recent sexual activity they reported on would be expected to include behaviors that influenced their decision to seek testing. Further, the study protocol called for the oversampling of HIV positive individuals and, in particular, recently infected HIV positive individuals . Thus, the generalizability of results presented in this study is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The MetroMates study also selectively enrolled men whose new HIV diagnosis suggested a recent or acute infection. As described by Gorbach et al [32], during the initial phase of enrollment, only men with a recent diagnosis were recruited. To complete enrollment, men with any new diagnosis, including chronically infected men, were recruited.…”
Section: Applicationmentioning
confidence: 99%